Sonic Apartheid: ecoracism, apartheid geographics and noise pollution in Cape Town's Blikkiesdorp - Watkins, Alexandra (University of Cape Town, 2020)
In Sonic Apartheid: Ecoracism, Apartheid Geographies, and Noise Pollution in Cape Town's Blikkiesdorp, Alexandra Downing Watkins begins a project of mapping geographies of dispossession and abandonment in Blikkiesdorp (Afrikaans for "Tin Can Town"), a Temporary Relocation Area on the margins of Cape Town created in 2007 following a wake of mass evictions for the 2010 World Cup. After being created as a "temporary" solution, Blikkiesdorp remained a site of abandonment where evicted peoples, refugees, and other "undesirables" were sent to live. Seven years later, the City of Cape Town and the Airports Company of South Africa signed a Memorandum of Understanding agreeing to realign one of the airport's runways, which would serve to relocate the community. Following the story of strategic organising by the Blikkiesdorp community to be included in the Environmental Impact Assessment that was being instrumentalized to further displace them, this work examines the community's struggle against conditions of abandonment through complicating the division of humans and the environment. This project engages with the mechanics of bio-, necro-, and geontopower, in contemporary South African environmental governance as an afterlife of apartheid spatial planning. The project features environmental research that was completed in cooperation with community members who shared their experiential environmental knowledge through interviews and diary entries as well as compiling decibel readings of excessive noise pollution. This data along with noise pollution diaries, photographs, and interviews has been compiled and placed in a digital archive in the form of an open-source ArchGIS Story Map. Combining theory and research contributed by the Blikkiesdorp community with the contemporary theoretical language of new materialism and critical race theory, this work engages with the porosity of bodies, the co-imbrication of bodies and landscape, how the creation of an "alternative social project" can serve to disturb and resist evidence-based technoscience and processes of ecoracist governance.